Visual impairment in very low birthweight children. Issue 2 (1st March 1997) - Powls, Andrew; Botting, Nicola; Cooke, Richard W I; Stephenson, Gail; Marlow, Neil
Abstract : AIMS: To compare the visual function of a cohort of very low birthweight (VLBW) children in early adolescence with that of their normal birthweight peers; to correlate visual impairment in this group with available perinatal data; and to examine the relation between the visual ability of VLBW children and their cognitive and motor skills. METHODS: As part of a long term neurodevelopmental study, 137 VLBW children and 163 normal birthweight controls were visually assessed between the ages of 11 and 13 years. Their eyes were examined for strabismus and movement disorders, and the use of visual correction for refractive errors was noted. Measures were made of visual acuity, stereopsis, and contrast sensitivity. All children had standardised tests of motor ability and cognitive skills. Perinatal data, including cranial ultrasonography results, had been obtained from the children's notes. No data were available however, regarding retinopathy of prematurity as screening was not established when these infants were born. RESULTS: On all measures, the visual function of the VLBW children was poorer than that of the controls. Reduced visual function was present in 63.5% of VLBW children compared with 36% of controls. Poor contrast sensitivity and strabismus were predictive of poor motor skills in the VLBW children. Poor contrast sensitivity and poor visual acuity (at 0.3 metres) were predictive of lower IQ. Low birthweight, intraventricular haemorrhage, intrauterine growth retardation and low 1 minute Apgar scores predicted reduced visual function. CONCLUSIONS: VLBW children have a high incidence of impaired vision. Stereopsis and contrast sensitivity are useful additions to the screening of this high risk group. They identified impaired vision that was not detected by normal screening and were related to impaired neurodevelopmental outcome.